Anatomical investigations of the Turkish critically endangered species : Achillea sivasica Çelik et Akpulat (Asteraceae) - Tekin, Mehmet (Array, 2020)
In this study, the root, stem, leaf midrib and leaf lamina anatomy and achene micromorphology of the Turkish critically endangered endemic Achillea sivasica were investigated for the first time. In this study, the root was found in late primary growth and in early secondary growth stage. It has a large cortex layer consisting of 12-16 cell rows beneath the periderm. Secretory ducts formed by 5-12 secretory cells embedded in the cortex and located near the vascular bundle were found at the root, which was in the early stage of secondary development. The stem was circular-pentagonal in cross-section. There was lamellar collenchyma beneath epidermis of pentagon corners, and cortex parenchyma between corners. Secretory ducts located near the phloem, between the cortex and endodermis on the interfascicular region, were also observed. An endodermis layer was evident and its cells have indentations and protrusions where they touch adjacent endodermis cells, which strengthens the connection between them. In addition, casparian strips were conspicuous in many endodermis cells. The leaf midrib area had a triangular cross section. There were secretory ducts, consisting of 4-5 secretory cells observed on both sides of the sclerenchymatous fibers that accompany the xylem. The leaf lamina was amphistomatic and stomata type was anomocytic. Mesophyll layer was equifacial. There was a large secretory duct and its diameter is bigger than the nearest main lamina vascular bundle. Achene shape of A. sivasica was lanceolate-oblong and its surface was ribbed and glabrous.